Controle de Bracon hebetor (Hymenoptera: Braconidae) em criação de Anagasta kuehniella (Lepidoptera: Pyralidae) - COSTA JUNIOR, Domicio D. P. (2015)
One of the main causes of loss in production Anagasta kuehniella (Lepidoptera: Pyralidae) in biofactories is the attack of a ectoparasitoid of larvae, the Bracon hebetor (Hymenoptera: Braconidae). The production of Anagasta kuehniella eggs in a biofactory can be reduced by 69% due to the attack of this ectoparasitoid. What can totally destroy an creation of these insects. The aim of this study was to evaluate a new method of creating the moth-the-flour (Anagasta kuehniella), aimed at isolating the parasitoid Bracon hebetor and compare the production of the creation method, already used (conventional), with the production of proposed method (experimental). To this end, it used sulfite role in trying to isolate the parasitoid Bracon hebetor, of creating Anagasta kuehniella, which it obtained 100% efficiency, while all plots of conventional treatment were attacked. With regard to production, there was no significant difference in the production of adult and eggs of Anagasta kuehniella in both the treatments. Both methods were efficient in the production and productivity. The proposed method was considered the most efficient in this work by effectively isolating the said parasitoid attacks da mass rearing of insect host.